Визначення ефективності повторного курсу медикаментозної терапії хворих на цукровий діабет із некритичною периферичною ангіопатією - Горобейко, М. Б. (Clinical Endocrinology and Endocrine Surgery, 2013)
The efficiency of Actovegin in cases of different stages of peripheral angiopathy in patients with diabetes mellitus on principles of evidence-based medicine using PEDIS classification was estimated. Levels of TcPO2 and speed of healing among patients with critical, non-crtitical ischemia and control groups were estimated before treatment, after 10, 45 days, 3 and 6 months and after secondary course of treatment (2nd course after 8-13 months after the 1st course). Actovegin prescribed intravenously 2000 mg/day during 12 days, than orally 600 mg daily up to 45 days. It was involved 39 patients who received 2 courses of treatment and control group 11 patients with traditional combine treatment of SDF. In control group TcPO2 increased from 35,7±4,31 to 39,77±8,22 mmHg compare with dynamic from 35,58±6,91 to 42,37±6,22 mmHg after 1st course of treatment and from 36,28±5,23 to 47,11±6,21 mmHg after the 2nd course of treatment. This improvement leads to healing 19 wounds after the 1st course and 8 wounds and active epitalization in 8 patients additionally after the 2nd course. So, general result after 2 courses is 84.6% of wound healing.